Dendritic cells in asthma - Lambrecht, Bart (Henry Stewart Talks, 2013)
The global immune response of the lungs, Dendritic cells (DCs): localisation, trafficking, probing for antigen, activation, behaviour in airways during asthma and inflammation, Controlling responsiveness to the node T cell area & Immunological synapse formation, Peptide presentation by MHC class II molecules, Cascade of costimulatory events, Th2 lymphocytes role in airway inflammation, Targeting DCs, Allergen exposure activation, Epithelial vs. DC expression of TLR4, Metabolic alterations, Uric acid and antigen sensitisation in mice, DC depletion, Basement membrane thickening in asthma, Model of chronic airway remodelling in the lungs, Collagen deposition & antigen uptake/recognition, Presentation of neoantigen